An Analysis of the Importance of Human Resource Management in Improving Employee Performance - Tambunan, Hotbona Novandi; Tanjung, Febrina Soraya; Siagian, Mei Veronika Sri Endang (Sean Institute, 2026)
Every business must manage its resources well to gain a competitive advantage and maintain long-term sustainability. Companies must ensure that their employees are satisfied and highly motivated. To conduct this research, this study employed a qualitative approach and examined the role of human resource management in improving employee work efficiency. This method was chosen because it allowed researchers to examine theories and previous research findings without collecting initial data. Human resource management is key to the success of modern organizations. Visionary HRM will create a cooperative, fair, and performance-based work culture, along with monitorable systems and procedures. Improving efficiency is crucial in an increasingly competitive business world. Consequently, company productivity depends on how systematic, professional, and results-oriented HR management.